2017
DOI: 10.5114/fmpcr.2017.65084
|View full text |Cite
|
Sign up to set email alerts
|

Moderate and severe pharyngitis in young adult inhabitants of Poznan, western Poland

Abstract: Background. acute pharyngitis is a frequent clinical problem. Objectives. To assess: the frequency of streptococcal etiology (β-hs) in moderate to severe pharyngitis among young adult patients, the accuracy of the centor score (cs) in predicting the likelihood of the β-hs etiology and the usefulness of the rapid antigen detection test (radT) in the appropriate selection of patients that ought to be treated with antibiotics. Material and methods. 202 individuals (101 patients and a sex-and age-matched control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…All the studies on managing pharyngitis were conducted in upper-middle or high-income countries. One study evaluated treatment choice 18 and five evaluated diagnostic strategy 19 23 . Four of the five studies that evaluated diagnostic strategies concluded that routine use of rapid antigen detection tests (RADTs) resulted in the lowest cost per case of accurate diagnosis and antibiotic treatment 19 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the studies on managing pharyngitis were conducted in upper-middle or high-income countries. One study evaluated treatment choice 18 and five evaluated diagnostic strategy 19 23 . Four of the five studies that evaluated diagnostic strategies concluded that routine use of rapid antigen detection tests (RADTs) resulted in the lowest cost per case of accurate diagnosis and antibiotic treatment 19 22 .…”
Section: Resultsmentioning
confidence: 99%
“…One study evaluated treatment choice 18 and five evaluated diagnostic strategy 19 23 . Four of the five studies that evaluated diagnostic strategies concluded that routine use of rapid antigen detection tests (RADTs) resulted in the lowest cost per case of accurate diagnosis and antibiotic treatment 19 22 . The other study evaluated backup testing for negative RADTs, concluding that it was of limited value 23 .…”
Section: Resultsmentioning
confidence: 99%